Analiza porównawcza SKS-ów - Dworaczek, Kamil (Pamięć i Sprawiedliwość, 2011)
The assassination of Stanisław Pyjas – collaborator of Workers’ Defence Committee [Komitet Obrony Robotników, KOR], originated a history of Student Solidarity Committees [Studencki Komitet Solidarności, SKS]. The first committee was founded in May 1977 in Cracow by the friends of the murdered and then – in 1977 and in 1978 in the following cities: Warsaw, Gdansk, Poznan, Wroclaw and Szczecin. In some regions the committees played major role on the regional map of pre-August 1980 political opposition. One could notice that older opposition such as KOR and the Movement for the Defense of Human and Civil Rights [Ruch Obrony Praw Człowieka i Obywatela, ROPCiO] hadsignificant influence on SKS’ activity, however the dependency level varied between particular committees. For example, those from Cracow, Wroclaw and Poznan, and most of all, the one from Warsaw, they were connected with the KOR, whereas those from Gdansk and Szczecin with the ROPCiO. An attempt to make a comparison between SKS’ activity in various fields like: their origins, hitherto history, undertaken actions, self-education process, publications, participation in the events of August 1980, enables historians to get familiar with what was characteristic (specific mechanisms) of the student opposition’s actionsin the 1970s. Moreover, those committees which were under the influence of the KOR bore several similarities one to each other. It leads to the conclusion that all activists of the student opposition were simultaneously members of the same movement. Hypothetically, but for the intensive Security Service’s actions aiming at reducing long-distance contacts between particular committees, it would have been possible to create a federation or even to set up a coordination body. Although it eventually did not succeed, it is still entitled saying that in reference to Warsaw, Cracow, Wroclaw and Poznan there was only one Student Solidarity Committee.